Student career centers measurement scale in higher education: exploratory and confirmatory factor analysis - Adha, Maulana Amirul; Wolor, Christian Wiradendi; Maisyaroh, Maisyaroh; Mustiningsih, Mustiningsih; Ansar, Rudy (Institute of Advanced Engineering and Science, 2024)
Previous research shows that measuring the quality of student career centers in higher education is not yet fully standardized and is often limited to qualitative approaches. The lack of valid and reliable measuring tools regarding the student career center can hamper efforts to improve and develop this service. The aim of the research is to develop and test a scale for measuring the quality of student career centers in the context of higher education. A quantitative approach with exploratory and confirmatory factor analysis (CFA) was used in this study, with respondents as many as 562 students from three different universities. Analysis and interpretation of the measurement scale evaluation was carried out in two stages, namely exploratory factor analysis (EFA) and continued with CFA. The research results identified that the dimensions of the role of career centers, utilization of career centers, management of workforce information, and fostering entrepreneurship are key elements that influence the effectiveness and impact of career centers in higher education. This scale can practically be used by each institution to evaluate the quality of the career centers they run, and can also be used by other researchers for further research.